Exploring Numeracy Skills in Algebra: A Cognitive Reasoning Analysis of Middle School Students in Indonesia - Sa’dah, Nella Rodiya; Afri, Lusi Eka; Nurrahmawati, Nurrahmawati; Arcat, Arcat (EDUPEDIA Publisher, 2025)
This study aims to describe the numeracy ability of students at the cognitive level of reasoning grade VIII State Junior High School 5 Rambah Hilir in solving algebraic domain numeracy problems. This study uses a qualitative approach with a descriptive type. The subjects in this study are students in grades VIII-3 of State Junior High School 5 Rambah Hilir which totals 23 students. Then 6 students with qualifications 2 students with high numeracy skills, 2 students with moderate numeracy skills and 2 students with low numeracy skills were selected as interview subjects. The technique of checking the validity of the data uses triangulation techniques. The results of the study showed that the numeracy ability of students at the cognitive level of reasoning at State Junior High School 5 Rambah Hilir, namely students with a high level of numeracy ability at the cognitive level of reasoning, were able to meet the three indicators of numeracy ability at the cognitive level of reasoning, namely namely analyzing data and information, evaluating, and inferring. Students with a level of numeracy ability at the cognitive level of moderate reasoning are only able to meet two indicators of numeracy ability at the cognitive level of reasoning, namely analyzing data and information, and evaluating. Students with a low level of numeracy ability at the cognitive level of reasoning are only able to meet one indicator of numeracy ability at the cognitive level of reasoning, namely analyzing data and information.